Front view of Harshat Mata Temple and Nandi shrine - Temples of India Project Team (Jio Institute, 2024)
Front view of Harshat Mata Temple and Nandi shrine (east). The original stone temple was built in the Mahameru style and was destroyed and replaced by a circular domed structure at a later period when the temple was reconstructed. The present temple has used broken fragments from the original temple in the foundation and pillars and a mix of modern materials in the dome and remaining parts.